2018
DOI: 10.1016/j.jbankfin.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Trading efficiency of fund families: Impact on fund performance and investment behavior

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Our cross-sectional study on fund performance is non-parametric, thus we do not tackle the causes on under performance. For example, the difference on performance may be explained by timing (Treynor & Mazuy, 1966;Henriksson & Merton, 1981;Andreu, Matallín-Sáez, & Sarto, 2018); investment style (Sharpe, 1992); the characteristics of the securities within mutual funds (Kent, Grinblatt, Titman, & Wermers, 1997); stock-picking talent, load fees, expenses and turnover (Wermers, 2002); portfolio holdings (Brinson & Fachler, 1985;Grinblatt & Titman, 1989a,1989bAndreu et al, 2018); trading efficiency (Cici, Dahm, & Kempf, 2018), and active management Grinold and Kahn (2000); Cremers and Petajisto (2009); Petajisto (2013); Crane and Crotty (2018). In this regard, besides the documentation of the relative performance of Colombian mutual funds, further parametric studies are needed to explore the causes and the differences of performance among funds.…”
Section: Resultsmentioning
confidence: 99%
“…Our cross-sectional study on fund performance is non-parametric, thus we do not tackle the causes on under performance. For example, the difference on performance may be explained by timing (Treynor & Mazuy, 1966;Henriksson & Merton, 1981;Andreu, Matallín-Sáez, & Sarto, 2018); investment style (Sharpe, 1992); the characteristics of the securities within mutual funds (Kent, Grinblatt, Titman, & Wermers, 1997); stock-picking talent, load fees, expenses and turnover (Wermers, 2002); portfolio holdings (Brinson & Fachler, 1985;Grinblatt & Titman, 1989a,1989bAndreu et al, 2018); trading efficiency (Cici, Dahm, & Kempf, 2018), and active management Grinold and Kahn (2000); Cremers and Petajisto (2009); Petajisto (2013); Crane and Crotty (2018). In this regard, besides the documentation of the relative performance of Colombian mutual funds, further parametric studies are needed to explore the causes and the differences of performance among funds.…”
Section: Resultsmentioning
confidence: 99%
“…Fund houses thus intervene in the managers' duties, and these interventions have the apparent purpose of enhancing the overall value of the fund house instead of maximising investors' investment value. Cici, Dahm, and Kempf (2018) examined how the efficiency of trading desks operated by mutual fund houses affect portfolio performance and investment behaviour of affiliated funds in the US.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fund families thus intervene into managers' duties, and these interventions have the apparent purpose of enhancing the overall value of the family instead of maximising investors' investment value. Cici et al (2018) examined "how the efficiency of trading desks operated by mutual fund families affected the portfolio performance and investment behaviour of affiliated funds in the US. Their results showed that by operating more efficient trading desks, trading costs could be reduced, and fund families could then significantly improve the performance of their funds and enable them to trade more and hold less liquid portfolios."…”
Section: B Performance Of Fund Familiesmentioning
confidence: 99%
“…Most mutual funds in the market are part of fund families. There are at least three reasons why this practice is prevalent (Cici et al, 2018). First, the family structure promotes economies of scale for the member funds' distribution, servicing, and promotion.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%